Sosialisasi Perda Nomor 2 Tahun 2015 Tentang Penyelenggaraan Bantuan Hukum Kepada Masyarakat Miskin Kecamatan Pasarwajo Kabupaten Buton - Darmawan Wiridin; Zulfikar Putra; Hado Hasina; Muh. Arifin (Jurnal Hukum dan Sosial Politik, 2023)
The existence of legal aid in a legal state is a necessity to provide legal assistance for the poor as mandated by the constitution. The implementation of the provision of legal aid to citizens is an effort to fulfill and at the same time as the implementation of a state of law that recognizes and protects and guarantees the human rights of citizens for the need for access to justice and equality before the law. The purpose of this service is to provide information to the community regarding the existence of legal aid for the poor in Pasarwajo Subdistrict This service activity is carried out in the form of lectures, questions and answers / discussions in which the speaker presents the material or presentation of the material then continues with a two-way discussion (question and answer). The findings obtained, that so far the community has not received complete information about legal assistance to the poor without being charged. After the socialization activity, the community, especially those in Pasarwajo Sub-district, had received information about legal aid. In addition, the activity was followed up with the formation of an institution that focuses on assisting legal cases affecting the poor in Pasarwajo Sub-district.